Impact of elevated temperature and water deficit on the chemical and sensory profiles of Barossa Shiraz grapes and wines - Bonada, Marcos; Jeffery, David William; Petrie, Paul R.; Moran, Martin; Sadras, Victor Oscar (Wiley, 2019)
Background and Aims: Interactions are the main causes of complexity in field experiments; however, no studies have combined water and temperature regimes in field‐growing vines. Here we assessed grape and wine attributes from a field trial where these factors were directly manipulated. Methods and Results: The experiment consisted of Shiraz vines grown in a 22 factorial experiment with two temperature (control and heated) and two water regimes (deficit and irrigated) during two seasons (2010/11 and 2011/12). The sensory and compositional characteristics of grapes and wines were assessed in both seasons, whereas a detailed profile of the phenolic substances was determined by spectrophotometry in 2011/12. We found additive effects (i.e. lack of interaction) between temperature and water for berry mass and components, fruit composition (titratable acidity and pH), grape phenolic substances (12.5% ethanol‐extracted and most of the 70% acetone‐extracted), wine phenolic substances (chemical age 2), and wine sensory traits (floral aromas and berry flavours). Significantly, previously unrecorded interactions between temperature and water were found for grape phenolic substances (70% acetone‐extracted skin and seed tannins and total phenolic substances per berry), wine phenolic substances (colour density, tannins and phenolic substances) and wine sensory traits (floral aromas, cooked fruit flavours and tannin structure). Conclusion: The effect of water deficit leading to colourful and flavoursome wines rich in phenolic substances may not be held under high temperature.